Analisis Perkembangan Kinerja Keuangan UMKM Dilihat Dari Optimalisasi Pengelolaan Bantuan Dana Desa dan Literasi Keuangan Pelaku UMKM (Studi Kasus UMKM Didesa Kubutambahan) - Ni Luh De Erik Trisnawati; Luh Puspita Dewi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This study aims to determine the development of MSME financial performance as seen from the optimization of village fund management and financial literacy of MSME actors in Kubu Additional Village. The population is all MSME actors who have received assistance in the form of funds from the village and the number of samples in this study is 41 MSME actors. The data analysis technique used in this study is the Structural Equation Modeling-SEM based on SEM variance, which is famously called Partial Least Square (PLS) visual version 3.0. The results of this study suggest that financial management does not have a significant effect on financial performance in MSMEs. Financial literacy does not moderate the influence of financial management on financial performance in this study.